A method to infer the three Cartesian wavelengths of a mountain wave from three soundings - Alexander, Pedro Manfredo (2010)
The number of atmospheric sounding techniques and the amount of missions within each of them continue to grow at the present time. The probability of having two or more profiles in a given region and time interval therefore is increasing. In the case of three close observations it would be a priori possible to infer the three Cartesian wavelengths of a mountain wave. However, the relative orientation of the three sounding paths cannot be arbitrary and must fulfill some conditions to avoid errors growing out of given bounds. © 2010 American Meteorological Society.